Clinical, pathological and loss of heterozygosity differences in Wilms tumors between Asian and non‐Asian children. Issue 6 (3rd December 2018) - Loke, Benjamin N.; Wong, Meng Kang; Tawng, Khawn D.; Kuick, Chick Hong; Jain, Sudhanshi; Lian, Derrick; Wagner, Elizabeth; Zou, Yuhan; Ganesan, Visveswari; Sim, Siam Wee; Lee, York Tien; Chin, Francis; et al.
Abstract : Wilms tumor demonstrates significant interethnic epidemiological, histological and outcome differences, and is rare and poorly studied among Asians. We compared the clinicopathological, and loss of heterozygosity (LOH) profile and survival outcomes of Asian and non‐Asian patients with Wilms tumor. Clinical charts and histological slides from patients with malignant renal tumors over a period of 20 years were retrospectively reviewed. We adapted a genotyping assay to determine 1p36 and 16q21‐22 LOH in formalin‐fixed paraffin‐embedded (FFPE) specimens, and compared these characteristics between Asian and non‐Asian patients. Fifty‐three (79.1%) Asian and 14 (20.9%) non‐Asian patients had Wilms tumors. Compared to non‐Asians, Asians were younger (mean 4.6 and 4.0 years, respectively), had more equal gender distribution (female: male = 1.8 and 1.0, respectively), fewer tumors with unfavorable histology (25.0% and 4.1%, respectively, p = 0.05), and less advanced disease at presentation, yet similar nodal metastases rates (16.7% and 18.4%, respectively). No Asian patients had bilateral tumors. Our adapted genotyping assay accurately determined LOH in FFPE specimens <10 years post‐fixation. Among 30 Asian patients, 1p and 16q LOH were each detected in 5 (16.7%) patients, respectively—similar to rates reported in other ethnicities. Yet after similar treatment with National Wilms Tumor Study regimens, 15‐year event‐free and overall survival for Asian patients was 95.7% and 96.3% respectively. In summary, despite similar nodal metastasis and LOH rates, Asian patients had fewer unfavorable histology tumors, lower‐stage disease, and better survival outcomes. The bases for these differences and implications on treatment strategy for these patients warrant further study. Abstract : What's new? Biomarkers identified so far in Wilms tumor have come from studying Caucasian patients. Here, the authors looked at the significance of these markers in Asians. To minimize the impact of cultural differences and treatment protocols, they studied patients in ethnically diverse Singapore. They analyzed tumors from 53 Asians and 14 non‐Asians. Both groups showed similar rates of loss of heterozygosity at 1p and 16q, and of nodal metastasis. Asian patients, however, had better histology, lower grade tumors, and higher survival. This suggests that 1p and 16q LOH may not be a useful biomarker for Wilms tumor risk stratification in Asians.